Effect Short–Term Biochar Application on Ultisol of Bengkulu, Indonesia - Prawito, P (KnE Life Sciences, 2019)
Most studies of biochar on agriculture were conducted in relatively short time period and generally showing positive effect. Couple studies however indicated that biochar application need long term to effect on both soil properties as well as plant growth and production. The purpose of this study was to evaluate the effect of short–term biochar application on Ultisol properties in Bengkulu. Research has been conducted on Ultisol in Kota Niur, Talang Empat, Bengkulu, Indonesia, since March 2013 to May 2014. The study was arranged in completely randomized block design with four treatments namely: A0 (control without biochar); A1 (burned biomass presence on each plot); A2 (wood charcoal of 120 t · ha, and A3 (coconut cell charcoal of 120 t · ha−1). All the treatments were repeated 12 times resulting in 48 experiment units. The recorded soil properties including bulk density, soil porosity, soil aggregate stability, water holding capacity, field soil moisture, air-dried soil moisture, soil pH, organic C, available N, P and K, as well as cation exchange capacity. All data were statistically analyzed using analysis of variance, F test with P < 0.05. All significant difference variables were analyzed using Duncan Multiple Range Test at P < 0.05. The result showed that two years application of 12 ton · ha−1 · yr−1 biochar did not significantly affect all soil properties studied, except available K. Coconut cell biochar showed best effect on available K (0.65 me · 100 g−1) compare with control (0.30 me · 100 g−1), burned existing biomass (0.39 me · 100 g−1), and wood biochar (0.33 me · 100 g−1). Keywords: Bengkulu, Biochar, Charcoal, Short-term biochar application, Ultisol.